2020
DOI: 10.1111/2041-210x.13511
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging spatial information to forecast nonlinear ecological dynamics

Abstract: There has been a recent demand for forecasting in ecology, particularly in the field of ecosystem management. Empirical dynamic modelling (EDM), an equation‐free nonlinear forecasting method, is receiving growing attention, but it requires long time series to produce accurate predictions. Though most ecological time series are short, spatial replicates are often available. Here we explore how utilizing available spatial data can improve our ability to forecast ecological dynamics. There are several ways to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 73 publications
(100 reference statements)
1
11
0
Order By: Relevance
“…We found that, in most cases, using age structure in a hierarchical or mixed age modeling approach improved predictive skill of models, both in empirical and simulated data. Our results are consistent with theory, which suggests that lags of additional age classes can stand in for unknown state variables (Munch et al 2017) analogously to incorporating spatial information (Johnson et al 2021) or information from additional species (Ye and Sugihara 2016).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found that, in most cases, using age structure in a hierarchical or mixed age modeling approach improved predictive skill of models, both in empirical and simulated data. Our results are consistent with theory, which suggests that lags of additional age classes can stand in for unknown state variables (Munch et al 2017) analogously to incorporating spatial information (Johnson et al 2021) or information from additional species (Ye and Sugihara 2016).…”
Section: Discussionsupporting
confidence: 89%
“…In reality, if maturation, survival, and growth are not constant (Gulland 1965;Hutchings 1993;Van der Veer et al 2000;Secor 2007;White et al 2014), then the time series of abundance from different ages will not maintain constant proportionality. Previous attempts to use additional information to improve prediction skill of short time series have emphasized that replicate groups (in this case age classes), must be similar enough so that their dynamics are mutually informative, but different enough to provide new information (Ye and Sugihara 2016;Munch et al 2017;Johnson et al 2021). We hypothesized that age-structured time series, in a sufficiently complex system, would contribute new information which will improve forecast skill relative to time series of a single age or total abundance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, this approach has been limited by requiring longtime series. Recent work shows that integrating an equation free non-linear approach with a Bayesian model can overcome the problem of short ecological time series (Johnson et al, 2020). To many in marine management, this concept is challenging despite recent work demonstrating the utility of this approach to a wide range of topics in marine ecology (Griffith, 2020).…”
Section: Whole-of-food Web Modelsmentioning
confidence: 99%